Emerging roles of Jab1/CSN5 in DNA damage response, DNA repair, and cancer - Pan, Yunbao (Landes Bioscience, 2014)
Jab1/CSN5 is a multifunctional protein that plays an important role in integrin signaling, cell proliferation, apoptosis, and the regulation of genomic instability and DNA repair. Dysregulation of Jab1/CSN5 activity has been shown to contribute to oncogenesis by functionally inactivating several key negative regulatory proteins and tumor suppressors. In this review, we discuss our current understanding of the relationship between Jab1/CSN5 and DNA damage and summarize recent findings regarding opportunities for and challenges to therapeutic intervention.